A new species of the elm powdery mildew species complex (Erysiphaceae) on Chinese elm (Ulmus parvifolia) in East Asia segregated from Erysiphe ulmi - Kirschner, Roland; Lotz-Winter, Hermine; Piepenbring, Meike (Phytotaxa, 2020)
Powdery mildews are common pathogens on wild elm trees as well as on planted ornamentals in Asia and Europe. The taxonomy of the powdery Erysiphe species on elms (Ulmus spp., Ulmaceae) is complicated by taxonomical changes and inconsistently labelled DNA data in databases and publications. Based on morphology and phylogenetic analysis of new collections from Germany and Taiwan, E. ulmi from Europe is revised, while specimens on U. parvifolia from East Asia revealed a separate clade indicating an undescribed species. Morphologically, both species can be distinguished by length of the foot cell of the conidiophore, whereas the teleomorph characteristics were not significantly distinctive.